ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF INNOVATIVE DEVELOPMENT OF SEED PRODUCTION (INNOVATIVE ECONOMY, 2024)
Radko V.I., Sytnyk V.H., Semysal A.V., Fedoruk Yu.V. ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF INNOVATIVE DEVELOPMENT OF SEED PRODUCTIONPurpose. The purpose of the article is to propose recommendations for the formation of models of innovative development of the seed industry based on the generalization of the research of scientists and the practical experience of the functioning of subjects of the seed industry.Methodology of research. The theoretical and methodological basis of the research is the dialectical method of cognition, a systematic approach to the study of economic phenomena, scientific developments of domestic and foreign scientists on issues of seed production, in particular. The following methods were used in the research process: abstract and logical - for the purpose of forming assumptions, hypotheses, as well as conclusions and generalizations; analysis and synthesis - when assessing the state of the seed industry and substantiating proposals for its improvement and ensuring full-fledged development in the future.Findings. On the basis of the conducted research, it was established that the current situation in the field of seed production is characterized by a violation of partnership relationships "science – seed companies – agricultural enterprises", does not provide a full understanding of the directions of its development, therefore, not only the in-depth study of the processes taking place, but also the improvement of the organizational and legal foundations of the formation and operation of the breeding and seed complex are substantiated.Originality. On the basis of the results, recommendations are proposed for the formation of development models of the seed industry, which can be presented as various organizational and legal forms of management and unite scientific institutions, agricultural enterprises and seed companies. Further development of the mentioned models can be carried out in the direction of creating an open agricultural and production (trade) business incubator.Practical value. The practical application of the recommendations will contribute to the formation of regional clusters in the field of seed production, which will ensure the formation of economic incentives for domestic scientists who are engaged in the breeding of new varieties of agricultural crops and their practical use in the technological process of farms of the corporate sector of the agrarian economy.Key words: system, seed production, innovation, development, selection, agricultural crops.
Keywords: system; seed production; innovation; development; selection; agricultural crops.